CircRNAs Are Here to Stay: A Perspective on the MLL Recombinome - Dal Molin, Anna; Bresolin, Silvia; Gaffo, Enrico; Tretti, Caterina; Boldrin, Elena; Meyer, Lueder H.; Guglielmelli, Paola; Vannucchi, Alessandro M.; te Kronnie, Geertruij; Bortoluzzi, Stefania (Frontiers in Genetics, 2019)
Chromosomal translocations harboured by cancer genomes are important oncogenic drivers. In MLL rearranged acute leukemia (MLLre) MLL/KMT2A fuses with over 90 partner genes. Mechanistic studies provided clues of MLL fusion protein leukemogenic potential, but models failed to fully recapitulate the disease. Recently, expression of oncogenic fusion circular RNAs (f-circ) by MLL-AF9 fusion was proven. This discovery, together with emerging data on the importance and diversity of circRNAs formed the incentive to study the circRNAs of the MLL recombinome. Through interactions with other RNAs, such as microRNAs, and with proteins, circRNAs regulate cellular processes also related to cancer development. CircRNAs can translate into functional peptides too. MLL and most of the 90 MLL translocation partners do express circRNAs and exploration of our RNA-seq dataset of sorted blood cell populations provided new data on alternative circular isoform generation and expression variability of circRNA of the MLL recombinome. Further, we provided evidence that rearrangements of MLL and three of the main translocation partner genes can impact circRNA expression, supported also by preliminary observations in leukemic cells. The emerging picture underpins the view that circRNAs are worthwhile to be considered when studying MLLre leukemias and provides a new perspective on the impact of chromosomal translocations in cancer cells at large.